2010
DOI: 10.20996/1819-6446-2010-6-6-865-869
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of the Statins in Preventing and Treating of the Coronary Heart Disease

Abstract: 865 ВведениеБолезни, связанные с атеросклерозом, занимают ос-новные позиции в структуре заболеваемости и смерт-ности в развитых странах. Дислипидемия -одна из ос-новных причин развития атеросклероза и ишемической болезни сердца (ИБС). Эпидемиологические иссле-дования свидетельствуют о прямой зависимости меж-ду уровнем общего холестерина (ХС), холестерина липопротеинов низкой плотности (ХСЛНП) и смерт-ностью вследствие ИБС.Статины -наиболее распространённый класс пре-паратов для лечения гиперхолестеринемии. Ста… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…All patients with acute coronary syndrome met the relevant diagnostic criteria in the guidelines for the diagnosis and treatment of acute ST-segment elevation myocardial infarction (2015) [ 11 ] and the guidelines for the diagnosis and treatment of non-ST-segment elevation acute coronary syndrome (2016) [ 12 ]. Patients with stable angina pectoris met the diagnostic criteria in the guidelines for the diagnosis and treatment of chronic stable angina pectoris [ 13 ], and selective coronary angiography showed that the coronary artery stenosis was more than 50% in single or multiple branches.…”
Section: Methodsmentioning
confidence: 99%
“…All patients with acute coronary syndrome met the relevant diagnostic criteria in the guidelines for the diagnosis and treatment of acute ST-segment elevation myocardial infarction (2015) [ 11 ] and the guidelines for the diagnosis and treatment of non-ST-segment elevation acute coronary syndrome (2016) [ 12 ]. Patients with stable angina pectoris met the diagnostic criteria in the guidelines for the diagnosis and treatment of chronic stable angina pectoris [ 13 ], and selective coronary angiography showed that the coronary artery stenosis was more than 50% in single or multiple branches.…”
Section: Methodsmentioning
confidence: 99%